ChemInform Abstract: Microwave‐Assisted Cycloaddition Reactions in Carbo‐ and Heterocyclic Chemistry. Issue 11 (March 2015) - Saber, Aziza; Marzag, Hamid; Benhida, Rachid; Bougrin, Khalid
Abstract Review: 137 refs.